Polar 3, 4-isoprene rubber with self-repairing function and preparation method thereof
The copolymerization of isoprene and polar α-olefins was catalyzed by the amidino rare earth catalyst system, and the problems of poor blending performance and lack of polar groups were solved, achieving polar 3,4-isoprene gels with high 3,4-selectivity and self-healing functions.
Patent Information
- Application Number
- CN202411932799.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing 3,4-isoprene glue has poor blending performance when kneading with fillers such as carbon black and lacks polar groups, making it difficult to achieve high 3,4-selectivity and self-healing functions.
The amidine rare earth catalyst system is adopted to adjust the insertion rate of polar α-olefins through the copolymerization of isoprene and polar α-olefins, and introduce oxygen or sulfur groups to improve the polarity and self-healing properties of the copolymer.
The high 3,4-selectivity and excellent self-healing function of polar 3,4-isoprene gel are achieved, improving its blending performance and service life with other polymers.
Smart Images

Figure CN119638893A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer preparation, and in particular to polar 3,4-isoamyl gum with self-repairing function and a preparation method thereof. Background Art
[0002] 3,4-isoprene rubber has good anti-skid performance and low sliding resistance due to its low double bond content in the main chain and a large number of side chains on the molecular chain. The tread rubber prepared with 3,4-isoprene rubber has excellent anti-skid performance and does not have the serious heat generation phenomenon of styrene-butadiene rubber, which can improve the safety performance of tire driving. Therefore, 3,4-isoprene rubber is an ideal rubber for preparing high-performance tire tread rubber, and it can also be used as a sealing material, anti-vibration material and polypropylene toughening modifier, so it has attracted much attention.
[0003] However, 3,4-isoprene gum lacks polar groups, and its blending performance is poor when mixed with fillers such as carbon black. People have studied functionalized 3,4-isoprene gum. For example, Diao Kaiying et al. used a single scandium cyclopentadienyl catalyst system to achieve the copolymerization of polar styrene and isoprene, and the 3,4-selectivity of the isoprene structural unit in the copolymer was 70% (Diao Kaiying. Copolymerization of styrene derivatives and conjugated dienes catalyzed by single scandium cyclopentadienyl catalyst [D]). In 2020, Sun Mengting et al. used a single scandium cyclopentadienyl catalyst system to achieve the copolymerization of isoprene and amine-functionalized pentene, and the 3,4-selectivity of the isoprene structural unit in the copolymer was 60-70%. (Sun Mengting. Study on the copolymerization of functionalized α-olefins and isoprene catalyzed by single scandium cyclopentadienyl catalyst [D]). However, the selectivity of 3,4-isoprene gum obtained in the above work is low. Therefore, it is urgent to develop a new catalytic system to obtain polar 3,4-isoprene gum with high 3,4-selectivity.
[0004] If 3,4-isoprene rubber is made self-healing, it will improve the service life, safety and environmental impact of tire rubber. The ultimate goal is to be able to create tough and autonomous self-healing polymers that can spontaneously repair mechanical damage in highly variable real-world environments without external intervention. Most of the self-healing polymers reported in the literature rely on reversible chemical interactions such as Diels-Alder reactions, hydrogen bonds, ion pair formation, and metal-ligand interactions. Such chemical interaction-based self-healing polymers usually require complex molecular design and cumbersome multi-step synthesis, and usually require the input of external energy or stimulation (such as heat, light or pressure) to achieve significant repair after mechanical damage. In addition, the chemical interactions used for the self-healing mechanism (such as hydrogen bonds, ion pair interactions, and metal-ligand interactions) may be destroyed in certain chemical environments (such as acidic or alkaline conditions), which may affect the self-healing performance. Summary of the invention
[0005] The present invention aims to solve the technical problems in the prior art and provide a polar 3,4-isoprene rubber with self-repairing function and a preparation method thereof. The insertion rate of polar α-olefin in the 3,4-isoprene rubber copolymer of the present invention can be arbitrarily adjusted according to the feed ratio of the monomers, and the introduction of oxygen-containing or sulfur-containing groups can increase the polarity of the copolymer, thereby increasing the blending performance of 3,4-isoprene rubber with other polymers. And the 3,4-isoprene rubber copolymer of the present invention also has excellent self-repairing function.
[0006] In order to solve the above technical problems, the technical solutions of the present invention are as follows:
[0007] A polar 3,4-isoamyl gum with self-repairing function, having a structure shown in general formula (I):
[0008]
[0009] In formula (I), E represents O or S;
[0010] R represents a substituent on the benzene ring, which is hydrogen, a C1-C20 alkyl group, a C6-C20 aryl group, a C1-C20 alkyl group containing halogen, or a halogen substituent; m represents the number of substituents R, which is an integer selected from 1 to 5. When m≥2, R is the same or different;
[0011] The ratio of x and y can take any value in the range of 0.1 to 1000;
[0012] The number average molecular weight of the polar 3,4-isoprene gum is 1×10 4 ~250×10 4 , the value of n is 30 to 10000.
[0013] In the above technical solution, the content of 3,4-structural units in the polar 3,4-isoprene gum is not less than 85%; the insertion rate of polar α-olefin structural units in the structure can be arbitrarily adjusted between 0.1% and 90%.
[0014] A method for preparing polar 3,4-isoamyl gum with self-repairing function comprises the following steps:
[0015] a) dispersing the amidine rare earth catalyst in an organic solvent under the protection of an inert gas such as nitrogen or argon to obtain a rare earth catalyst solution;
[0016] b) using isoprene and polar α-olefin as monomer raw materials, catalyzing a polymerization reaction with the rare earth catalyst solution obtained in step a), terminating the polymerization reaction after a certain polymerization time, and settling and drying the product to obtain polar 3,4-isoprene gum;
[0017] The structural formula of the polar α-olefin monomer is shown in the general formula (III):
[0018]
[0019] Wherein, E represents O or S;
[0020] R represents a substituent on the benzene ring, which is hydrogen, a C1-C20 alkyl group, a C6-C20 aryl group, a C1-C20 alkyl group containing a halogen, or a halogen substituent; m represents the number of substituents R, which is an integer selected from 1 to 5. When m≥2, R is the same or different.
[0021] In the above technical solution, the polar α-olefin monomer is selected from one of the AW structures:
[0022]
[0023]
[0024] In the above technical solution, the rare earth catalyst is composed of three parts: A, B and C. Among them, A is a rare earth complex, which is a complex shown in formula (II):
[0025]
[0026] In formula (II), R1 is a substituent of the amidine carbon, which is a C1-C20 aryl group, a C1-C20 aryl group containing halogen, a C1-C20 alkyl group or a C1-C20 alkyl group containing halogen;
[0027] R2 and R3 are substituents on the nitrogen atom, and are each independently a C1-C20 aryl group, a C1-C20 aryl group containing halogen, a C1-C20 alkyl group, or a C1-C20 alkyl group containing halogen;
[0028] The rare earth metal Ln is selected from Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb or Lu;
[0029] R4 and R5 are each independently a C1-C10 alkyl group, a C1-C10 silyl group, a C1-C10 silylamine group, a C1-C10 alkylamine group, or a C3-C10 allyl group;
[0030] L is tetrahydrofuran, ether, ethylene glycol dimethyl ether or toluene; m is 0, 1 or 2;
[0031] B is an organoboron reagent selected from [Ph3C][B(C6F5)4], [PhNMe2H][BPh4], [NEt3H][BPh4], [PhNMe2H][B(C6F5)4] or B(C6F5)3;
[0032] C is an alkyl aluminum compound selected from: alkyl aluminum or aluminoxane.
[0033] In the above technical scheme, R1 is phenyl, p-methylphenyl, p-ethylphenyl, p-isopropylphenyl, p-tert-butylphenyl, benzyl, m-methylphenyl, m-ethylphenyl, m-isopropylphenyl, mesitylene, 2,6-dimethylphenyl, 2,6-diethylphenyl, mesitylene or 2,6-diisopropylphenyl;
[0034] R2 and R3 are each independently phenyl, p-methylphenyl, p-ethylphenyl, p-isopropylphenyl, p-tert-butylphenyl, benzyl, m-methylphenyl, m-ethylphenyl, m-isopropylphenyl, mesitylene, mesitylene, mesitylene, 2,6-dimethylphenyl, 2,6-diethylphenyl, 2,6-diisopropylphenyl, 2,6-diethyl-4-methylphenyl, 2,6-diethyl-4-tert-butylphenyl, 2,6-diisopropyl-4-methylphenyl, 2,6-di-tert-butyl-4-methylphenyl, 2,6-diphenylphenyl, 2,6-ditrifluoromethylphenyl, 2-fluorophenyl, 3-trifluoromethylphenyl, p-trifluoromethylphenyl or p-fluorophenyl;
[0035] R4 and R5 are each independently CH3, CH2SiMe3, CH(SiMe3)2, N(SiMe3)2, NH(SiMe3) or 1,3-C3H5;
[0036] B is [Ph3C][B(C6F5)4] or [PhNMe2H][B(C6F5)4];
[0037] C is trimethylaluminum, triethylaluminum, tri-n-propylaluminum, tri-n-butylaluminum, triisopropylaluminum, triisobutylaluminum, tripentylaluminum, trihexylaluminum, tricyclohexylaluminum, trioctylaluminum, triphenylaluminum, tri-p-tolylaluminum, tribenzylaluminum, ethyldibenzylaluminum, ethyldi-p-tolylaluminum, diethylbenzylaluminum, dimethylaluminum hydride, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, diisopropylaluminum hydride, diisobutylaluminum hydride, dipentylaluminum hydride, dihexylaluminum hydride, dicyclohexylaluminum hydride, dioctylaluminum hydride, diphenylaluminum hydride, di-p-tolylaluminum One or more of tolylaluminum hydride, dibenzylaluminum hydride, ethylbenzylaluminum hydride, ethyl-p-tolylaluminum hydride, dimethylaluminum chloride, diethylaluminum chloride, di-n-propylaluminum chloride, di-n-butylaluminum chloride, diisopropylaluminum chloride, diisobutylaluminum chloride, dipentylaluminum chloride, dihexylaluminum chloride, dicyclohexylaluminum chloride, dioctylaluminum chloride, diphenylaluminum chloride, di-p-tolylaluminum chloride, dibenzylaluminum chloride, ethylbenzylaluminum chloride, ethyl-p-tolylaluminum chloride, methylaluminoxane, ethylaluminoxane, n-propylaluminumoxane and n-butylaluminoxane.
[0038] In the above technical solution, the organic solvent is selected from one or a mixture of saturated alkanes, aromatic hydrocarbons, halogenated aromatic hydrocarbons, and cycloalkanes.
[0039] In the above technical solution, the organic solvent is selected from one or a mixture of toluene, xylene, benzene, n-hexane, n-heptane, cyclohexane, chlorobenzene, dichlorobenzene and trichlorobenzene.
[0040] In the above technical scheme, the molar ratio of the polar α-olefin monomer to the rare earth complex having the structure of formula (II) is (50-10000):1; the molar ratio of the isoprene monomer to the rare earth complex having the structure of formula (II) is (50-10000):1; the molar ratio of the organic boron salt to the rare earth complex having the structure of formula (II) is (0.5-2.0):1; the molar ratio of the alkyl aluminum compound to the rare earth complex having the structure of formula (II) is (0.5-3000):1.
[0041] In the above technical solution, the polymerization reaction temperature is -60 to 80°C, and the polymerization reaction time is 0.5 to 48 hours.
[0042] The beneficial effects of the present invention are:
[0043] The insertion rate of polar α-olefin in the polar 3,4-isoprene copolymer with self-repairing function of the present invention can be arbitrarily adjusted according to the feed ratio of monomers, and the introduction of oxygen- or sulfur-containing groups can increase the polarity of the copolymer, thereby increasing the blending performance of 3,4-isoprene and other polymers. In addition, the 3,4-isoprene copolymer of the present invention also has excellent self-repairing function.
[0044] The invention discloses a method for preparing polar 3,4-isoprene gum with self-repairing function. The catalyst combination used is a rare earth complex, an alkyl aluminum compound and an organic boron salt. The invention is the first to use an amidine rare earth catalyst to synthesize polar 3,4-isoprene gum containing oxygen or sulfur. The insertion rate of polar α-olefin structural units in the copolymer can be arbitrarily adjusted between 1% and 99%, breaking through the previous limitation of low insertion rate of functionalized monomers in copolymers. The polymer has excellent self-repairing function. Therefore, the method for preparing polar 3,4-isoprene gum provided by the invention is very innovative. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0046] Figure 1 This is the NMR image of polar 3,4-isoamyl gum obtained in Preparation Example 6 of the present invention.
[0047] Figure 2This is a GPC characterization chart of the polar 3,4-isoamyl gum obtained in Preparation Example 6 of the present invention.
[0048] Figure 3 This is a schematic diagram of the self-repairing ability experiment of the polar 3,4-isopentyl gum with self-repairing function of the present invention.
[0049] Figure 4 This is a self-healing tensile curve diagram of the polar 3,4-isoprene gum obtained in Preparation Example 1 of the present invention. DETAILED DESCRIPTION
[0050] The polar 3,4-isoamyl gum with self-repairing function of the present invention has a structure of general formula (I):
[0051]
[0052]
[0053] In the formula, E represents O or S; R represents a substituent on the benzene ring, which is hydrogen, a C1-C20 alkyl group, a C6-C20 aryl group, a C1-C20 alkyl group containing halogen, or a halogen substituent; m represents the number of substituents R, which is an integer selected from 1 to 5, and when m≥2, R is the same or different;
[0054] The ratio of x and y can take any value in the range of 0.1 to 1000;
[0055] The polar 3,4-isoprene gum with self-repairing function of the present invention also has the following characteristics: the number average molecular weight of the polar 3,4-isoprene gum is 1×10 4 ~250×10 4 , n value is 30 to 10000. The content of 3,4-structural units in the polar 3,4-isoprene is not less than 85%. The insertion rate of polar α-olefin structural units in the copolymer can be arbitrarily adjusted between 0.1% and 90%.
[0056] The method for preparing polar 3,4-isoamyl gum with self-repairing function of the present invention comprises the following steps:
[0057] a) dispersing the amidine rare earth catalyst in an organic solvent under the protection of an inert gas such as nitrogen or argon to obtain a catalyst solution;
[0058] b) Using polar α-olefin and isoprene as monomer raw materials, according to a certain monomer feed ratio, using the catalyst solution obtained in step a) to catalyze the polymerization reaction, terminating the polymerization reaction after a certain polymerization time, and settling the product and drying it to obtain polar 3,4-isoprene gum with self-repairing function. The polymerization reaction can be carried out in the presence of a solvent for solution polymerization, or in the absence of a solvent for bulk polymerization.
[0059] The polar α-olefin monomer has a structure of general formula (III):
[0060]
[0061] In the formula, E represents O or S; R represents a substituent on the benzene ring, which is hydrogen, a C1-C20 alkyl group, a C6-C20 aryl group, a C1-C20 alkyl group containing halogen, or a halogen substituent; m represents the number of substituents R, which is an integer selected from 1 to 5, and when m≥2, R is the same or different;
[0062] Preferably, the polar α-olefin monomer is one of the structures shown in A to W:
[0063]
[0064] The rare earth catalyst of the present invention is composed of three parts: A, B and C:
[0065] Wherein, A is a rare earth complex, which is a complex represented by formula (II):
[0066]
[0067] In the general formula (II), R1 is a substituent of the amidine carbon, which is a C1-C20 aryl group, a C1-C20 halogen-containing aryl group, a C1-C20 alkyl group or a C1-C20 halogen-containing alkyl group, preferably a phenyl group, a p-methylphenyl group, a p-ethylphenyl group, a p-isopropylphenyl group, a p-tert-butylphenyl group, a benzyl group, a m-methylphenyl group, a m-ethylphenyl group, a m-isopropylphenyl group, a mesitylene trimethylphenyl group, a 2,6-dimethylphenyl group, a 2,6-diethylphenyl group, a mesitylene triethylphenyl group or a 2,6-diisopropylphenyl group.
[0068] R2 and R3 are substituents on the nitrogen atom, each of which is independently a C1-C20 aryl group, a C1-C20 aryl group containing halogen, a C1-C20 alkyl group or a C1-C20 alkyl group containing halogen, and is preferably a phenyl group, a p-methylphenyl group, a p-ethylphenyl group, a p-isopropylphenyl group, a p-tert-butylphenyl group, a benzyl group, a m-methylphenyl group, a m-ethylphenyl group, a m-isopropylphenyl group, a mesitylene trimethylphenyl group, a mesitylene triethylphenyl group, a mesitylene triisopropylphenyl group, a 2,6-dimethylphenyl group, a 2,6-diethylphenyl group, a 2,6-diisopropylphenyl group, a 2,6-diethyl-4-methylphenyl group, a 2,6-diethyl-4-tert-butylphenyl group, a 2,6-diisopropyl-4-methylphenyl group, a 2,6-di-tert-butyl-4-methylphenyl group, a 2,6-diphenylphenyl group, a 2,6-ditrifluoromethylphenyl group, a 2-fluorophenyl group, a 3-trifluoromethylphenyl group, a p-trifluoromethylphenyl group or a p-fluorophenyl group.
[0069] The rare earth metal Ln is selected from Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb or Lu;
[0070] R4 and R5 are each independently selected from a C1-C10 alkyl group, a C1-C10 silyl group, a C1-C10 silylamine group, a C1-C10 alkylamine group or a C3-C10 allyl group, preferably CH3, CH2SiMe3, CH(SiMe3)2, N(SiMe3)2, NH(SiMe3) or 1,3-C3H5.
[0071] L is tetrahydrofuran, diethyl ether, ethylene glycol dimethyl ether or toluene; m=0, 1 or 2.
[0072] B is an organic boron reagent selected from [Ph3C][B(C6F5)4], [PhNMe2H][BPh4], [NEt3H][BPh4], [PhNMe2H][B(C6F5)4] or B(C6F5)3, preferably [Ph3C][B(C6F5)4] or [PhNMe2H][B(C6F5)4].
[0073] The molar ratio of the organic boron salt to the rare earth complex having the structure of formula (II) is (0.5-2.0):1.
[0074] C is an alkylaluminum compound, and the alkylaluminum compound is selected from: alkylaluminum or aluminoxane; further, the alkylaluminum is preferably alkylaluminum hydride or alkylaluminum chloride, and further preferably, the alkylaluminum compound is trimethylaluminum, triethylaluminum, tri-n-propylaluminum, tri-n-butylaluminum, triisopropylaluminum, triisobutylaluminum, tripentylaluminum, trihexylaluminum, tricyclohexylaluminum, trioctylaluminum, triphenylaluminum, tri-p-tolylaluminum, tribenzylaluminum, ethyldibenzylaluminum, ethyldi-p-tolylaluminum, diethylbenzylaluminum, dimethylaluminum hydride, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, diisopropylaluminum hydride, diisobutylaluminum hydride, dipentylaluminum hydride , dihexylaluminum hydride, dicyclohexylaluminum hydride, dioctylaluminum hydride, diphenylaluminum hydride, di-p-tolylaluminum hydride, dibenzylaluminum hydride, ethylbenzylaluminum hydride, ethyl-p-tolylaluminum hydride, dimethylaluminum chloride, diethylaluminum chloride, di-n-propylaluminum chloride, di-n-butylaluminum chloride, diisopropylaluminum chloride, diisobutylaluminum chloride, dipentylaluminum chloride, dihexylaluminum chloride, dicyclohexylaluminum chloride, dioctylaluminum chloride, diphenylaluminum chloride, di-p-tolylaluminum chloride, dibenzylaluminum chloride, ethylbenzylaluminum chloride, ethyl-p-tolylaluminum chloride, methylaluminoxane, ethylaluminoxane, n-propylaluminum chloride and n-butylaluminoxane.
[0075] The molar ratio of the alkyl aluminum compound to the rare earth complex having the structure of formula II is (0.5-3000):1.
[0076] When solution polymerization is adopted, the organic solvent is selected from one or a mixture of saturated alkanes, aromatic hydrocarbons, halogenated aromatic hydrocarbons, and cycloalkanes, preferably toluene, xylene, benzene, n-hexane, n-heptane, cyclohexane, chlorobenzene, dichlorobenzene, and trichlorobenzene.
[0077] The molar ratio of the polar α-olefin monomer to the rare earth complex having the structure of formula (II) is (50-10000):1; the molar ratio of the isoprene monomer to the rare earth complex having the structure of formula (II) is (50-10000):1; the feed ratio of the polar α-olefin monomer to the isoprene monomer can be adjusted arbitrarily.
[0078] The monomer concentration of the polar α-olefin monomer is 1 to 60 g / 100 mL; the monomer concentration of the isoprene monomer is 1 to 60 g / 100 mL.
[0079] The polymerization reaction temperature is -60 to 80°C, and the polymerization reaction time is 0.5 to 48 hours.
[0080] A specific embodiment of the method for preparing polar 3,4-isoamyl gum with self-repairing function of the present invention is as follows:
[0081] A solution of the coordination catalytic system composed of the rare earth complex, alkyl aluminum compound and organic boron salt is placed in a polymerization container after anhydrous and oxygen-free treatment; polar α-olefin monomer and isoprene monomer are added at the same time, the molar ratio of the added polar α-olefin monomer to the rare earth complex in the coordination catalytic system is 50:1-10000:1, the molar ratio of the added isoprene monomer to the rare earth complex in the coordination catalytic system is 50:1-10000:1, the feeding ratio of the polar α-olefin monomer to the isoprene monomer can be adjusted arbitrarily, the polymerization reaction is carried out at -60-80°C for 0.5-48 hours, a hydrochloric acid ethanol solution with a volume concentration of 10% is added to terminate the polymerization reaction, the reaction solution is poured into methanol for precipitation, and polar 3,4-isoprene gum is obtained; and the obtained polymer is placed in a vacuum drying oven for drying to obtain polar 3,4-isoprene gum with a constant dry weight.
[0082] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention rather than limiting the claims of the present invention.
[0083] According to the present invention, the rare earth catalyst combination includes a rare earth complex, an alkyl aluminum compound and an organic boron salt; the catalyst is a coordination catalytic system containing a variety of compounds. The rare earth complex used in the following examples is a complex represented by formula (II), wherein the rare earth complex having the structure of formula (II) is preferably a complex represented by formula 1 to formula 15.
[0084]
[0085]
[0086] According to the present invention, the preparation method of the catalyst is: rare earth complex, alkyl aluminum compound and organic boron salt are uniformly mixed in an organic solvent according to a proportion to obtain a homogeneous catalyst. The organic solvent is selected from one or a mixture of saturated alkanes, aromatic hydrocarbons, halogenated aromatic hydrocarbons and cycloalkanes. Toluene, xylene, benzene, n-hexane, n-heptane, cyclohexane, chlorobenzene, dichlorobenzene and trichlorobenzene are preferred.
[0087] Preparation Example of Catalyst Combination:
[0088] Preparation of catalyst combination 1: At 25°C, 10 μmol of the rare earth complex of formula 1, 10 μmol [Ph3C][B(C6F5)4], 100 μmol triisobutylaluminum and 5 mL toluene solvent were added to a 25 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 2.0 mmol·L –1 , react for 2 minutes to obtain catalyst combination 1.
[0089] Preparation of catalyst combination 2: At 25°C, 10 μmol of the rare earth complex of formula 2, 10 μmol [Ph3C][B(C6F5)4], 100 μmol triisobutylaluminum and 5 mL toluene solvent were added to a 25 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.67 mmol·L –1 , react for 2 minutes to obtain catalyst combination 2.
[0090] Preparation of catalyst combination 3: At 0°C, 10 μmol of the rare earth complex shown in formula 2, 10 μmol [Ph3C][B(C6F5)4], 100 μmol triisobutylaluminum and 5 mL toluene solvent were added to a 25 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.67 mmol·L –1 , react for 2 minutes to obtain catalyst combination 3.
[0091] Preparation of catalyst combination 4: At -60°C, 10 μmol of the rare earth complex of formula 2, 10 μmol [Ph3C][B(C6F5)4], 100 μmol triisobutylaluminum and 5 mL toluene solvent were added to a 25 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.67 mmol·L –1 , react for 2 minutes to obtain catalyst combination 4.
[0092] Preparation of catalyst combination 5: At 40°C, 10 μmol of the rare earth complex of formula 2, 10 μmol [Ph3C][B(C6F5)4], 100 μmol triisobutylaluminum and 5 mL toluene solvent were added to a 25 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.67 mmol·L –1 , react for 2 minutes to obtain catalyst combination 5.
[0093] Preparation of catalyst combination 6: At 80°C, 10 μmol of the rare earth complex of formula 2, 10 μmol [Ph3C][B(C6F5)4], 100 μmol triisobutylaluminum and 5 mL toluene solvent were added to a 25 mL polymerization container that had been treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.67 mmol·L –1 , react for 2 minutes to obtain catalyst combination 6.
[0094] Preparation of catalyst combination 7: At 25°C, 10 μmol of the rare earth complex shown in formula 3, 10 μmol [PhNHMe2][B(C6F5)4], 200 μmol triethylaluminum and 10 mL of hexane solvent were added to a 25 mL polymerization container that had been treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 1.0 mmol·L –1 , react for 2 minutes to obtain catalyst combination 7.
[0095] Preparation of catalyst combination 8: At -40°C, 10 μmol of the rare earth complex of formula 4, 10 μmol [Ph3C][B(C6F5)4], 100 μmol triisobutylaluminum and 10 mL toluene solvent were added to a 50 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 1.0 mmol·L –1 , react for 2 minutes to obtain catalyst combination 8.
[0096] Preparation of catalyst combination 9: At 25°C, 10 μmol of the rare earth complex of formula 5, 10 μmol [Ph3C][B(C6F5)4], 100 μmol triisobutylaluminum and 10 mL pentane solvent were added to a 50 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.5 mmol·L –1 , react for 2 minutes to obtain catalyst combination 9.
[0097] Preparation of catalyst combination 10: At 60°C, 10 μmol of the rare earth complex of formula 6, 10 μmol [PhNHMe2][B(C6F5)4], 1 mmol of triisobutylaluminum and 10 mL of xylene solvent were added to a 25 mL polymerization container that had been treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 1.0 mmol·L –1 , react for 2 minutes to obtain catalyst combination 10.
[0098] Preparation of catalyst combination 11: At 25°C, 10 μmol of the rare earth complex of formula 7, 10 μmol [Ph3C][BPh4], 10 mmol of triisobutylaluminum and 5 mL of hexane solvent were added to a 50 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.2 mmol·L –1 , react for 2 minutes to obtain catalyst combination 11.
[0099] Preparation of catalyst combination 12: At 0°C, 10 μmol of the rare earth complex of formula 8, 20 μmol [PhNHMe2][BPh4], 5 mmol of triisobutylaluminum and 5 mL of hexane solvent were added to a 50 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.25 mmol·L –1 , react for 2 minutes to obtain catalyst combination 12.
[0100] Preparation of catalyst combination 13: At 80°C, 10 μmol of the rare earth complex of formula 9, 10 μmol of B(C6F5)3, 100 μmol of triisobutylaluminum and 5 mL of hexane solvent were added to a 50 mL polymerization container that had been treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.2 mmol·L –1 , react for 2 minutes to obtain catalyst combination 13.
[0101] Preparation of catalyst combination 14: At 0°C, 10 μmol of the rare earth complex represented by formula 10, 10 μmol [Ph3C][B(C6F5)4], 500 μmol of triisobutylaluminum and 5 mL of xylene solvent were added to a 50 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.25 mmol·L –1 , react for 2 minutes to obtain catalyst combination 14.
[0102] Preparation of catalyst combination 15: At 40°C, 10 μmol of the rare earth complex represented by formula 11, 10 μmol [PhNHMe2][B(C6F5)4], 100 μmol trimethylaluminum and 10 mL toluene solvent were added to a 50 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.33 mmol·L –1 , react for 2 minutes to obtain catalyst combination 15.
[0103] Preparation of catalyst combination 16: At 25°C, 10 μmol of the rare earth complex represented by formula 12, 10 μmol [NEt3H][BPh4], 100 μmol trimethylaluminum and 10 mL of xylene solvent were added to a 25 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.25 mmol·L –1 , react for 2 minutes to obtain catalyst combination 16.
[0104] Preparation of catalyst combination 17: At -60°C, 10 μmol of the rare earth complex of formula 13, 10 μmol [Ph3C][BPh4], 100 μmol triisobutylaluminum and 5 mL of hexane solvent were added to a 50 mL polymerization container that had been treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.25 mmol·L –1 , react for 2 minutes to obtain catalyst combination 17.
[0105] Preparation of catalyst combination 18: At 80°C, 10 μmol of the rare earth complex represented by formula 14, 10 μmol [Ph3C][BPh4], 30 mmol of methylaluminoxane and 5 mL of toluene solvent were added to a 100 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.2 mmol·L –1 , react for 2 minutes to obtain catalyst combination 18.
[0106] Preparation of catalyst combination 19: At 0°C, 10 μmol of the rare earth complex of formula 15, 10 μmol [Ph3C][B(C6F5)4], 20 μmol of diisobutylaluminum hydride and 5 mL of chlorobenzene solvent were added to a 50 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.2 mmol·L –1 , react for 2 minutes to obtain catalyst combination 19.
[0107] Preparation of catalyst combination 20: At 25°C, 10 μmol of the rare earth complex represented by formula 15, 10 μmol [Ph3C][B(C6F5)4], 100 μmol of methylaluminoxane and 10 mL of chlorobenzene solvent were added to a 50 mL polymerization container treated with anhydrous and oxygen-free conditions. The concentration of the rare earth complex in the catalyst combination was 0.2 mmol·L –1 , react for 2 minutes to obtain catalyst combination 20.
[0108] Example of preparing polar 3,4-isoprene rubber with self-repairing function by copolymerization of polar α-olefin and isoprene:
[0109] Example 1
[0110] 5 mL of toluene solution of catalyst combination 1 was taken and placed in a polymerization bottle treated with anhydrous and oxygen-free conditions, and 5.0 mmol of polar α-olefin monomer A and 5.0 mmol of isoprene monomer were added. The polymerization reaction was carried out at 25°C for 4 hours, and 2 mL of ethanol solution with a volume concentration of 10% hydrochloric acid was added to terminate the polymerization reaction. The reaction solution was poured into 100 mL of methanol for precipitation to obtain a phenoxy-functionalized polar 3,4-polyisoprene copolymer; the obtained copolymer was then placed in a vacuum drying oven and dried for 48 hours to obtain a dry constant weight phenoxy-functionalized polar 3,4-polyisoprene with a net weight of 1.19 g. The total conversion rate was 95%. The results of hydrogen nuclear magnetic spectroscopy ( 1 HNMR) and C-NMR ( 13 C NMR) analysis showed that the syndiotacticity of the phenoxy-functionalized polar 3,4-polyisoprene was greater than 99%; the insertion rate of the polar α-olefin monomer in the copolymer was 54%; the number average molecular weight (M) of the phenoxy-functionalized polar 3,4-polyisoprene was obtained by GPC analysis. n ) is 80,000, and the molecular weight distribution (M w / M n ) is 1.48. The glass transition temperature (T) of phenoxy-functionalized polar 3,4-polyisoprene was obtained by DSC analysis. g ) is 7℃.
[0111] Example 2-61
[0112] Examples 2-61 are examples of the coordination catalytic system provided by the present invention in the copolymerization of polar α-olefins and isoprene. Figure 1 This is the NMR characterization image of polar 3,4-isoamyl gum prepared in Example 6. The steps are the same as those in Example 1, and the specific conditions and results obtained are shown in Table 1:
[0113] Table 1 Synthesis of polar 3,4-isoprene glue with self-healing function by coordination polymerization method
[0114]
[0115]
[0116]
[0117] From the polymerization data of Examples 1 to 61 of the copolymerization of polar α-olefin and isoprene, it can be concluded that when the copolymerization of polar α-olefin and isoprene is catalyzed by the rare earth catalyst combination provided by the present invention through the coordination polymerization method, the conversion of polar α-olefin monomer and isoprene monomer can be 71% to 100%. The number average molecular weight of the polar 3,4-isoprene polymer is between 1×10 4 ~250×10 4 In the range of molecular weight distribution, the molecular weight distribution is 1.1 to 3.0 (attached Figure 2 ). The rare earth catalyst combination has a high adaptability to temperature. In the polymerization temperature range of -60 to 80°C, the insertion rate of polar α-olefin structural units in the copolymer can be arbitrarily adjusted between 0.1% and 90%. However, since the insertion of polar α-olefin monomers in the copolymer is not conducive to the crystallization of the polymer, most copolymers have no melting point.
[0118] The contact angle is an important indicator for characterizing the polarity of a polymer. The smaller the contact angle, the greater the polarity of the polymer. We tested the contact angle of the prepared partial polar α-olefin and isoprene copolymer and pure 3,4-isoprene gum. The contact angle test results of the partial polar α-olefin and isoprene copolymer are shown in Table 1. The contact angle test result of pure 3,4-isoprene gum is 100°. Compared with pure 3,4-isoprene gum, the contact angle of the polar α-olefin and isoprene copolymer of the present invention is smaller, and the polarity of the copolymer increases with the increase of the content of the polar α-olefin structural unit.
[0119] Tensile tests can measure a series of strength and plasticity indicators of materials. Strength usually refers to the ability of a material to resist elastic deformation, plastic deformation and fracture under external force. We conducted tensile tests on polar 3,4-isoprene rubber, as shown in the attached figure. Figure 3 As shown, it was cut off and subjected to a tensile test again after being repaired at room temperature for a period of time. The results are shown in Table 2. Figure 4This is a self-repair tensile curve of the polar 3,4-isoprene gum obtained in Example 1, indicating that the polar 3,4-isoprene gum has good self-repair function.
[0120] Table 2. Test of self-healing function of polar 3,4-isoprene gum
[0121]
[0122]
[0123] The above is a detailed introduction to the preparation method of polar 3,4-isopentyl gum with self-healing ability provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified. These improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A polar 3,4-isoprene gum with self-repairing function, characterized in that: It has the structure shown in the general formula (Ⅰ): In formula (I), E represents O or S; R represents a substituent on the benzene ring, which is hydrogen, a C1-C20 alkyl group, a C6-C20 aryl group, a C1-C20 alkyl group containing halogen, or a halogen substituent; m represents the number of substituents R, which is an integer selected from 1 to 5. When m≥2, R is the same or different; The ratio of x and y can take any value in the range of 0.1 to 1000; The number average molecular weight of the polar 3,4-isoprene gum is 1×10 4 ~250×10 4 , n value is 30~10000.
2. The polar 3,4-isoamyl gum with self-repairing function according to claim 1, characterized in that: The content of 3,4-structural units in the polar 3,4-isoprene gum is not less than 85%; the insertion rate of polar alpha-olefin structural units in the structure can be arbitrarily adjusted between 0.1% and 90%.
3. A method for preparing polar 3,4-isoamyl gum with self-repairing function according to claim 1 or 2, characterized in that: The following steps are involved: a) dispersing the amidine rare earth catalyst in an organic solvent under the protection of an inert gas such as nitrogen or argon to obtain a rare earth catalyst solution; b) using isoprene and polar α-olefin as monomer raw materials, catalyzing a polymerization reaction with the rare earth catalyst solution obtained in step a), terminating the polymerization reaction after a certain polymerization time, and settling and drying the product to obtain polar 3,4-isoprene gum; The structural formula of the polar α-olefin monomer is shown in the general formula (III): Wherein, E represents O or S; R represents a substituent on the benzene ring, which is hydrogen, a C1-C20 alkyl group, a C6-C20 aryl group, a C1-C20 alkyl group containing a halogen, or a halogen substituent; m represents the number of substituents R, which is an integer selected from 1 to 5. When m≥2, R is the same or different.
4. The method for preparing polar 3,4-isoamyl gum with self-repairing function according to claim 3, characterized in that: The polar α-olefin monomer is selected from one of the AW structures:
5. The method for preparing polar 3,4-isoamyl gum with self-repairing function according to claim 3, characterized in that: The rare earth catalyst consists of three parts: A, B and C composition: Wherein, A is a rare earth complex, which is a complex represented by formula (II): In formula (II), R1 is a substituent of the amidine carbon, which is a C1-C20 aryl group, a C1-C20 aryl group containing halogen, a C1-C20 alkyl group or a C1-C20 alkyl group containing halogen; R2 and R3 are substituents on the nitrogen atom, and are each independently a C1-C20 aryl group, a C1-C20 aryl group containing halogen, a C1-C20 alkyl group, or a C1-C20 alkyl group containing halogen; The rare earth metal Ln is selected from Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb or Lu; R4 and R5 are each independently a C1-C10 alkyl group, a C1-C10 silyl group, a C1-C10 silylamine group, a C1-C10 alkylamine group, or a C3-C10 allyl group; L is tetrahydrofuran, ether, ethylene glycol dimethyl ether or toluene; m is 0, 1 or 2; B is an organoboron reagent selected from [Ph3C][B(C6F5)4], [PhNMe2H][BPh4], [NEt3H][BPh4], [PhNMe2H][B(C6F5)4] or B(C6F5)3; C is an alkyl aluminum compound selected from: alkyl aluminum or aluminoxane.
6. The method for preparing polar 3,4-isoamyl gum with self-repairing function according to claim 5, characterized in that: R1 is phenyl, p-methylphenyl, p-ethylphenyl, p-isopropylphenyl, p-tert-butylphenyl, benzyl, m-methylphenyl, m-ethylphenyl, m-isopropylphenyl, mesitylene, 2,6-dimethylphenyl, 2,6-diethylphenyl, mesitylene or 2,6-diisopropylphenyl; R2 and R3 are each independently phenyl, p-methylphenyl, p-ethylphenyl, p-isopropylphenyl, p-tert-butylphenyl, benzyl, m-methylphenyl, m-ethylphenyl, m-isopropylphenyl, mesitylene, mesitylene, mesitylene, 2,6-dimethylphenyl, 2,6-diethylphenyl, 2,6-diisopropylphenyl, 2,6-diethyl-4-methylphenyl, 2,6-diethyl-4-tert-butylphenyl, 2,6-diisopropyl-4-methylphenyl, 2,6-di-tert-butyl-4-methylphenyl, 2,6-diphenylphenyl, 2,6-ditrifluoromethylphenyl, 2-fluorophenyl, 3-trifluoromethylphenyl, p-trifluoromethylphenyl or p-fluorophenyl; R4 and R5 are each independently CH3, CH2SiMe3, CH(SiMe3)2, N(SiMe3)2, NH(SiMe3) or 1,3-C3H5; B is [Ph3C][B(C6F5)4] or [PhNMe2H][B(C6F5)4]; C is trimethylaluminum, triethylaluminum, tri-n-propylaluminum, tri-n-butylaluminum, triisopropylaluminum, triisobutylaluminum, tripentylaluminum, trihexylaluminum, tricyclohexylaluminum, trioctylaluminum, triphenylaluminum, tri-p-tolylaluminum, tribenzylaluminum, ethyldibenzylaluminum, ethyldi-p-tolylaluminum, diethylbenzylaluminum, dimethylaluminum hydride, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, diisopropylaluminum hydride, diisobutylaluminum hydride, dipentylaluminum hydride, dihexylaluminum hydride, dicyclohexylaluminum hydride, dioctylaluminum hydride, diphenylaluminum hydride, di-p-tolylaluminum One or more of tolylaluminum hydride, dibenzylaluminum hydride, ethylbenzylaluminum hydride, ethyl-p-tolylaluminum hydride, dimethylaluminum chloride, diethylaluminum chloride, di-n-propylaluminum chloride, di-n-butylaluminum chloride, diisopropylaluminum chloride, diisobutylaluminum chloride, dipentylaluminum chloride, dihexylaluminum chloride, dicyclohexylaluminum chloride, dioctylaluminum chloride, diphenylaluminum chloride, di-p-tolylaluminum chloride, dibenzylaluminum chloride, ethylbenzylaluminum chloride, ethyl-p-tolylaluminum chloride, methylaluminoxane, ethylaluminoxane, n-propylaluminumoxane and n-butylaluminoxane.
7. The method for preparing polar 3,4-isoamyl gum with self-repairing function according to claim 3, characterized in that: The organic solvent is selected from saturated alkanes, aromatic hydrocarbons, halogenated aromatic hydrocarbons, cycloalkanes or a mixture of several thereof.
8. The method for preparing polar 3,4-isoamyl gum with self-repairing function according to claim 7, characterized in that: The organic solvent is selected from the group consisting of toluene, xylene, benzene, n-hexane, n-heptane, cyclohexane, chlorobenzene, dichlorobenzene, trichlorobenzene, or a mixture of the two or more thereof.
9. The method for preparing polar 3,4-isoamyl gum with self-repairing function according to claim 5, characterized in that: The molar ratio of the polar α-olefin monomer to the rare earth complex having the structure of formula (II) is (50-10000):1; the molar ratio of the isoprene monomer to the rare earth complex having the structure of formula (II) is (50-10000):1; the molar ratio of the organic boron salt to the rare earth complex having the structure of formula (II) is (0.5-2.0):1; the molar ratio of the alkyl aluminum compound to the rare earth complex having the structure of formula (II) is (0.5-3000):
1.
10. The method for preparing polar 3,4-isoamyl gum with self-repairing function according to claim 3, characterized in that: The polymerization reaction temperature is -60 to 80°C, and the polymerization reaction time is 0.5 to 48 hours.
Citation Information
Patent Citations
High 3,4-polyconjugated diene with unsaturated group on side arm and preparation method thereof, and high 3,4-polyconjugated diene with functional group on side arm and preparation method thereof
CN106397648A
Production method for polar olefin polymer and copolymer
CN110418807A
Molded product comprising polarized olefin-based polymer and property thereof
CN111868111A
Self-repairing of polyisoprene through microstructure control using rare earth catalyst
JP2024022574A
Allyl ether compound, resin composition thereof, cured product thereof, and method for producing allyl ether compound
WO2023276760A1